4 - L’Aide et les priorités internes des politiques agricoles nationales et sa place dans le secteur agricole: Le cas du Bénin: by Machioudi Dissou - Machioudi Disso (Africa Development, 1992)
Benin enjoyed food self-sufficiency in the 1970s as a result of its policy emphasis on food production. In the 80s however donor agencies induced a significant readjustment of priorities in agricultural production as evidenced by a growing concentration on industrial crops such as cotton. The experience in Benin underscores the fact that international aid is a tool to redirect or adjust agricultural policies to donor interests. Throughout the 80s Benin received aid from the World Bank, the EEC and the United Nations. In addition, three types of bilateral aid were received from a large number of Western countries including Japan, Eastern Block countries and Africa. It is interesting to note that aid from African countries namely Nigeria, Libya and Algeria was double that from the socialist countries and equivalent with that from multinational agencies. Of this a significant portion was tied-aid whereby the recipient country has to buy equipment and related services from the donor country. For example, the three biggest bilateral donors to Benin's agricultural sector, West Germany 39%, France 62% and USA 77% of the total aid was earmarked as tied-aid. Contrary to the conception of cooperation between two partners, aid sustains inegalitarian relations in which the weight of the recipient is minimal even in situations where there is a strong political will to avoid the hardships and dependence that aid engenders.